A Case of Secondary Epiretinal Membrane Spontaneous Release - Andrey N. Andreev; Alexey V. Bushuev; Sergey N. Svetozarskiy (Case Reports in Ophthalmological Medicine)
Purpose. To report a rare case of secondary epiretinal membrane (ERM) spontaneous separation with subsequent visual restoration. Case Summary. We are reporting a case with the history of branch retinal vein occlusion, peripheral retinal neovascularization, and retinal photocoagulation. Our examination revealed secondary ERM associated with relatively high visual acuity (0.6), and a watchful waiting strategy was chosen. During the follow-up, slight visual deterioration, progressive deformation of the retinal profile, and an increase in diffuse retinal edema were observed. No surgical or laser treatment was performed. On the next visit, the spontaneous ERM separation with residual parapapillary fixation, the increase in visual acuity (0.9), and the decrease in retinal thickness were revealed. Conclusion. Such cases present additional evidence to a deferral surgical strategy for the management of patients with ERM and relatively high visual acuity.